A model of political selection for good governance in Africa - Adewole Musiliu Adeolu (International Journal of Management, Economics and Social Sciences (IJMESS), 2017)
This paper sought to outline mechanisms for selecting high quality leaders into public office having identified the failure of political leadership as the bane of economic development and democracy in Africa. In the first stage of the screening process, certain elements of costs are imposed on the intending politicians so as to deter the entry of dishonest politicians into politics. This is accomplished via the inverse relationship between the degree of honest and the costs of participation. The unique thing is that separating equilibrium that makes participation costs zero for honest individuals and heavy for their dishonest counterparts could in principle be obtained. Interestingly the mechanisms that generate information about the past of intending politicians also impose heavy costs on groups which supply this information. This process should yield an equilibrium that includes only honest and competent politicians in the political system, leading to more accelerate economic development.
Keywords: D69; D73; N37; 330; Leadership failure; participation costs; pooling equilibrium; separating equilibrium; screening costs; social welfare